International Instruments Related to Industrial Property: An Empirical Analysis and a Case Study (European Journal of Marketing and Economics, 2018)
Along with its independence from the former Yugoslav Federation, the Republic of Macedonia opened a new chapter in reforming herself politically and economically and with the overall reforms in the law system, changes also happened in the field of Industrial Property. Proper measures were taken for its protection by establishing SOIP – the Country’s State Office of Industrial Property, firstly known as the Office for the Protection of Industrial Property, within the Macedonian Ministry of Development, to later become an autonomous legal entity under the Government, according to the adopted Law on Industrial Property of 2002. The new Law and Institution further strengthened and enforced legal protection of IP rights by taking care of and handling disputes related to IP protection. Requests for the protection and acquisition of industrial property rights, such as patent requests, registration of trademarks, industrial designs, geographical indications or topographies of integrated circuits can be addressed by the abovementioned laws and Institution. Main functions of the State Office of Industrial Property are implementing the law and regulations, ratification of international agreements, creation of proper conditions for an efficient protection of Industrial Property in accordance with standards set by agreements and international industrial property institutions, such as WIPO and it also appears as a mechanism to help the growth of economic, social and cultural prosperity. The rights derived from a scientific or artistic work are also foreseen and encouraged by the Country’s Constitution, in order to promote and help the technological development and a free market for everyone concerned.
Keywords: Industrial Property, TRIPS, Copyright, IP Laws, IP Protection.